Análise Estatística Da Duração Dos Alofones De /b d g/ Em Espanhol LE (PERcursos Linguísticos, 2022)
From experimental research, we statistically analyzed 532 sounds from 20 spontaneous speech interviews with Brazilian FL Spanish teachers from the State of Rio de Janeiro applying the two-tailed Student test t methodology. The results obtained in a statistical and percentage way, point to the existence of a hybrid sound that would correspond to a kind of hinge between the making of the /b d g/ in Spanish FL allophones of our informants and the standard data obtained from the bibliography consulted from these sounds for Spanish MT.